2004
DOI: 10.1097/01.alc.0000148099.12344.c8
|View full text |Cite
|
Sign up to set email alerts
|

Galanin Microinjection in the Third Ventricle Increases Voluntary Ethanol Intake

Abstract: These data show that galanin injected in the third ventricle increases EtOH consumption and that the effect can occur during both the light and the dark periods of the diurnal cycle in the presence of food and water. This suggests that galanin may play a role in augmenting voluntary alcohol intake and perhaps the development of alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 36 publications
1
54
0
Order By: Relevance
“…Also, 2 recent studies from our laboratories show that PVN or i.c.v. injection of GAL can increase ethanol consumption, and a GAL receptor antagonist can produce the opposite effect: a marked decrease in ethanol intake (Lewis et al, 2004;Rada et al, 2004). This suggests a possible cause-and-effect relationship, in the form of a positive feedback circuit, between the peptides and ethanol, similar to that seen for fat.…”
Section: Functional Consequences Of Increased Peptide Expressionmentioning
confidence: 90%
See 2 more Smart Citations
“…Also, 2 recent studies from our laboratories show that PVN or i.c.v. injection of GAL can increase ethanol consumption, and a GAL receptor antagonist can produce the opposite effect: a marked decrease in ethanol intake (Lewis et al, 2004;Rada et al, 2004). This suggests a possible cause-and-effect relationship, in the form of a positive feedback circuit, between the peptides and ethanol, similar to that seen for fat.…”
Section: Functional Consequences Of Increased Peptide Expressionmentioning
confidence: 90%
“…Recent studies indicate a similar relationship between hypothalamic GAL and the consumption of ethanol. Injection of GAL into the PVN or ventricles increases the amount of ethanol consumed (Lewis et al, 2004;Rada et al, 2004), and voluntary ethanol intake and systemic injection of ethanol stimulate the expression of GAL mRNA in the PVN (Leibowitz et al, 2003). These results suggest that peptides in the hypothalamus that modulate food intake may also have a role in ethanol intake.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, fat-rich diets increase galanin expression in the hypothalamus (Leibowitz, Akabayashi, & Wang, 1998). Based on these data, Lewis, Johnson, Waldmen, Leibowitz, & Hoebel (2004) investigated the role of galanin on alcohol intake. They found that in rats trained to prefer alcohol over water for many weeks, microinjection of this 29-30 amino acid peptide into the third ventricle near the paraventricular nucleus (PVN) (Lewis et al) or in the nucleus itself (Rada, Avena, Leibowitz, & Hoebel, 2004) increased alcohol intake.…”
Section: Development Of Alcohol Dependence: the Role Of Feeding Nutrmentioning
confidence: 99%
“…18 Ethanol intake increases GAL mRNA expression in the rat hypothalamus, 19 whereas GAL injected into the third ventricle or the hypothalamus increases ethanol consumption in rats that have learned to drink alcohol at moderate levels. 20,21 This suggests the possibility of a positive feedback loop between GAL and alcohol intake. 22 The gene encoding preprogalanin, GAL, localized on chromosome 11q13.2, 23 is 7.5 kb in length.…”
Section: Introductionmentioning
confidence: 99%